Application of bioceramic endodontic sealers in clinical practice - Stefanova, Vesela; Zhekov, Kostadin; Raycheva, Ralitsa (Journal of the Pakistan Medical Association, 2023)
Objective: To assess the attitude of dental medicine practitioners towards the usage of bioceramic endodontic sealers in their clinical practice. Method: The survey-based study was conducted from March 2019 to February 2020 in Plovdiv, Bulgaria, after approval from the ethics review committee of the Medical University of Plovdiv, and comprised dentists of either gender who attended in person events organised by the Bulgarian Dental Association. Data was collected using a self-reporting 20-item questionnaire. Data was analysed using SPSS 26. Results: Of the 200 forms distributed, 164(82%) were duly filled; 52(32%) from males and 112(68%) from females. The overall median age was 46.50 years (interquartile range: 21 years). Mean work experience was 23.68±11.43 years. Significant differences were found between the application of bioceramic sealers and the type of acquired specialty, the endodontic obturation technique and the final irrigation solution (p<0.05). Conclusion: Majority of the respondents did not feel the need to change the endodontic obturation technique in order to adopt the usage of bioceramic sealers. Key Words: Bioceramic sealer, Attitude, Dentists, Survey.